2003
DOI: 10.1079/bjn2003994
|View full text |Cite
|
Sign up to set email alerts
|

Tomatoes have natural anti-thrombotic effects

Abstract: The prevention of arterial thrombotic diseases has a high priority in developed countries. An inappropriate diet may be an important risk factor for thrombotic events. The daily intake of an anti-thrombotic diet may offer a convenient and effective way of prevention. The aim of the present study was to test tomato extracts for anti-thrombotic effects and to identify those varieties that have such an effect. A shear-induced platelet-function test (haemostatometry) was used to test anti-thrombotic potential in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 28 publications
8
53
0
3
Order By: Relevance
“…It has been observed that the tomato has platelet antiaggregation activity in vitro and in vivo by inhibiting platelet aggregation induced by ADP and collagen (75)(76)(77)(78)(79)(80). This finding has also been confirmed by our research group (71).…”
Section: Tomatoes: Platelet Anti-aggregation Activity and Endothelialsupporting
confidence: 74%
“…It has been observed that the tomato has platelet antiaggregation activity in vitro and in vivo by inhibiting platelet aggregation induced by ADP and collagen (75)(76)(77)(78)(79)(80). This finding has also been confirmed by our research group (71).…”
Section: Tomatoes: Platelet Anti-aggregation Activity and Endothelialsupporting
confidence: 74%
“…The antiplatelet activity ex vivo was similar to that observed by Yamamoto et al, who showed that intake of tomato components with in vitro antiplatelet activity affects ex vivo platelet function in a dose-dependent manner. 21 Meanwhile, O'Kennedy et al observed antiplatelet activity 3 h after eating tomato fractions. 12 Given the involvement of platelets in atherogenesis, from early stages of this process, together with other cardioprotective functions of bioactive compounds in tomatoes, and reduction of low density lipoprotein and decreased blood pressure.…”
Section: Abcmentioning
confidence: 99%
“…21 The aqueous extract of pomace, compared with aqueous extracts of fresh tomatoes and pasta, showed greater inhibitory activity of platelet aggregation. The aqueous extract of pomace, compared with aqueous extracts of fresh tomatoes and pasta, showed greater inhibitory activity of platelet aggregation.…”
mentioning
confidence: 96%
“…Tests were performed in vitro and evaluated in vivo, by testing laser-induced thrombosis in mice. One of the tomato varieties tested (KG99-4) showed a significant antithrombotic activity both in vitro and in vivo, inhibiting not only thrombus formation but also showing a thrombolytic effect [98]. The intake of tomato products is effective in preventing lipid peroxidation, a risk factor for atherosclerosis and CVD.…”
Section: Hypercholesterolemia and Cvdmentioning
confidence: 99%